National Chi Nan University's Role in Dark-Sky Governance and Regional Revitalization: A Model of Local Engagement and International Vision - Tseng, Yung Ping; Jiang, You Zih (Journal of Sustainability Perspectives, 2025)
National Chi Nan University (NCNU) integrates local engagement with global perspectives, advancing University Social Responsibility (USR) initiatives to support regional development. A key example is NCNU’s role in Hehuan Mountain Dark-Sky Park, Taiwan’s first internationally certified dark-sky park, promoting sustainable tourism and environmental conservation. Taiwan’s tourism industry struggles to balance economic growth with sustainability. In Qingjing, short-stay tourism strains local resources. NCNU collaborated with governments and astronomy associations to develop dark-sky tourism (DST) as a solution to extend visitor stays while preserving ecology. NCNU helped draft the Hehuan Mountain Dark-Sky Park Management Ordinance, aligning lighting regulations with International Dark-Sky Association (IDA) standards. The university fostered cooperation among government agencies, businesses, and astronomy experts to balance conservation with economic benefits. DST integration into hospitality services encouraged eco-friendly tourism, while star-guiding programs built local expertise. Beyond dark-sky governance, NCNU supports regional revitalization in healthcare, Indigenous tourism, and AI-driven smart agriculture. By training professionals and fostering sustainable industries, NCNU strengthens economic resilience, positioning Hehuan Mountain as a global research hub for light pollution studies.